Highly reduced survival in essential thrombocythemia and polycythemia vera patients with vascular complications during follow‐up. (28th January 2020) - Ahlstrand, Erik; Samuelsson, Jan; Lindgren, Marie; Pettersson, Helna; Liljeholm, Maria; Ravn‐Landtblom, Anna; Scheding, Stefan; Andréasson, Björn
Abstract: Objective: To explore the relative importance of risk factors, treatments, and blood counts for the occurrence of vascular complications and their impact on life expectancy in essential thrombocythemia (ET) and polycythemia vera (PV). Methods: Nested case‐control study within the Swedish MPN registry. From a cohort of 922 ET patients and 763 PV patients, 71 ET and 81 PV cases with vascular complications were compared with matched controls. Results: Incidence of vascular complications was 2.0 and 3.4 events per 100 patient‐years in ET and PV, respectively. At diagnosis, no significant risk factor differences were observed between cases and controls in neither of the diseases. At the time of vascular event, ET complication cases did not differ significantly from controls but in PV, cases had significantly higher WBCs and were to a lesser extent treated with anti‐thrombotic and cytoreductive therapy. Life expectancy was significantly decreased in both ET and PV cases compared with controls. Conclusions: The risk of vascular complications is high in both ET and PV, and these complications have a considerable impact on life expectancy. The protective effect of anti‐thrombotic and cytoreductive therapy for vascular complications in PV underscores the importance of avoiding undertreatment.